PENGARUH PEMUPUKAN PADA BUDIDAYA JAGUNG AHUKLEAN DI BESIKAMA, BELU, NTT - Charles Y Bora; B Murdolelono (Research Center for Biology-Indonesian Institute of Sciences, 2006)
Influence of fertililizing to Ahuklean corn cultivation was done in Fahiluka Village, Malaka Tengah Sub-district, Belu District, East Nusa Tenggara Province, during hot season, between August to November 2003. The aim of this research to get appropriate fertilizing method in ahuklean corn cultivation. The research was laid in RBD with 8 treatments of fertilizing and 3 replications.The size of plot treatment was 10 m x 10 m, plant distance was 100 cm x 40 cm, using Hybrid Pioneer corn variety with 3 seeds/hole. Parameters to be observed including growth and production, plant height at 15 days old, 45 days old, stem diameters; length and diameter of corn swollen, yield of dry grain and weight per 1000 grain. Results showed that fertilizing is not significantly influence the vegetative growth but corn yield and weigth per 1000 grain. The urea 100 kg/ha + SP-36 50 kg/ha with drilled method beside plant (PI) giving higher yield i.e. 4,50 t/ha. Using PPC Greentonic in 2 times spread (P7) is assumed as an alternative for ahuklean corn fertilizing, because it is able to increase the yield production up to 3,47 t/ha.